Security in wireless ad hoc network. (2017) - Ubarhande, Sachin D.; Doye, Dharmpal D.; Nalwade, Prakash S.
The mobile ad hoc network is open medium, easy to deploy and free of the centralised control network. But these features of mobile ad hoc network come along with security attacks, such as black hole attack and grey hole attack. In black hole attack malicious node degrades security and performance of network. This paper proposes a dual identity-based intrusion detection system to improve security and performance of mobile ad hoc network. The proposed system works based on the head node identities, namely, base and virtual. The head node uses the virtual identity to detect the malicious nodes and serves source node to establish a secure path to destination node. The simulation conducted using the network simulator revealed that proposed system improves the performance of the network for packet delivery ratio by 5%, throughput by 43%, packet loss rate by 57% and routing overhead by 13% as compared to another system.